THE DSS 'PLANNING KIT' AND ITS APPLICATION IN THE SPANKRACHT* STUDY - A.G. Kors (International Association of Lowland Technology, 2004)
The Netherlands is expected to face severe consequences of climate change. A rise of the average sea level with 60 cm and increase with about 20% of the extreme discharges of the rivers Rhine and Meuse might be expected ad the end of this century. This requires measures. Therefore a policy analyses has been carried out to determine which strategy could be followed to maintain the current safety satndards. In this policy analyses about three hundred spatial measures were evaluated. To support the work a Decision Support System has been developed: the Planning Kit. This article presents the Planning Kit and ilustrates working with the Planning Kit. In the Spankracht study the Planning Kit proved to be an indispensable instrument in the evaluation process.